2016
DOI: 10.1111/1541-4337.12211
|View full text |Cite
|
Sign up to set email alerts
|

d‐Mannose: Properties, Production, and Applications: An Overview

Abstract: d-Mannose is a C-2 epimer of d-glucose, which is a natural monosaccharide. It can be obtained from both plants and microorganisms. Chemical synthesis and biotransformation of d-mannose from d-fructose or d-glucose by using d-mannose isomerases, d-lyxose isomerases, and cellobiose 2-epimerase were intensively studied. d-Mannose is an important component of polysaccharides and glycoproteins. It has been widely used in the food, pharmaceutical, and poultry industries, acting as the source of dietary supplements, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
115
1
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(135 citation statements)
references
References 136 publications
6
115
1
7
Order By: Relevance
“…[13] As shown in the Scheme 1, SBFAwere efficient for aerobic NAD + regeneration in vitro, and the order of catalytic activity of these SBFAappeared to be F1 > F2 > F4 > F3,w hich agrees well with our previous reports. Recently,sugars like d-mannose have been getting increasing attention for health care and pharmaceutical interests due to its potential biological activities.…”
supporting
confidence: 88%
“…[13] As shown in the Scheme 1, SBFAwere efficient for aerobic NAD + regeneration in vitro, and the order of catalytic activity of these SBFAappeared to be F1 > F2 > F4 > F3,w hich agrees well with our previous reports. Recently,sugars like d-mannose have been getting increasing attention for health care and pharmaceutical interests due to its potential biological activities.…”
supporting
confidence: 88%
“…As an essential glyconutrient for human health, mannose is a popular nutritional and health-beneficial food supplement (Hu et al, 2016). It has been reported that mannose can act as a prebiotic, with beneficial effects on bowel functions and dysbiosis of the microecology in the human body (Umemura, Asano, Hoshino, & Iino, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is an important glyconutrient for human health, and is recommended as a dietary supplement for infants and children. 6 In addition, it is also a key ingredient or intermediate for the synthesis of antitumor agents, 7 immunostimulatory agents, 8 auxiliary moisturizing agents, 9 D-mannitol, 10 and vitamins. 11 Furthermore, D-mannose is an effective additive in animal feeds, which can inhibit the growth of intestinal pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Although several chemical synthesis processes of D-mannose from D-glucose have been reported, the reaction temperature and acid concentration are under strict control. 6 In addition, all the drawbacks of the chemical methods, including the sophisticated purification processes, application safety, and the chemical waste and by-product, make it become less desirable. 13 As a result, the enzymatic approaches to D-mannose production have recently gained researchers' attention.…”
Section: Introductionmentioning
confidence: 99%